2021
DOI: 10.1111/ssqu.12949
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Addiction, Loneliness, Narcissistic Personality, and Family Belonging Among University Students: A Path Analysis

Abstract: Background. The relationship between smartphone addiction (SPA) and loneliness is examined in several studies, however, the mediating effects of the variables related to narcissism and the family on the relationship between SPA and loneliness are not yet available in the literature. Objective. The present study investigates the role of SPA on loneliness and the moderating effects of narcissistic personality and family belonging on loneliness. Participants and Setting. Data required for research were obtained v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 114 publications
0
13
0
1
Order By: Relevance
“…At the same time, we found that high scores of Narcissisms were related to lower conflicts with the addictive use of mobile phones. Although people with predominant Narcissism traits tend to spend more time using their mobile phones (Gökçearslan, Yildiz, Berikan, & Saritepeci, 2021), previous studies have also reported an inverse relationship between Narcissisms and the addictive behavior to mobile phones (Hussain, Griffiths, & Sheffield, 2017).…”
Section: Discussionmentioning
confidence: 93%
“…At the same time, we found that high scores of Narcissisms were related to lower conflicts with the addictive use of mobile phones. Although people with predominant Narcissism traits tend to spend more time using their mobile phones (Gökçearslan, Yildiz, Berikan, & Saritepeci, 2021), previous studies have also reported an inverse relationship between Narcissisms and the addictive behavior to mobile phones (Hussain, Griffiths, & Sheffield, 2017).…”
Section: Discussionmentioning
confidence: 93%
“…Majority of participants in most studies were women and ages ranged from 12 to 99 years, with two studies focusing on adolescents aged 12 to 19 years (24,42). Many studies focused exclusively on community samples of people with traits/a diagnosis of 'emotionally unstable personality disorder' or traits of 'narcissistic personality' and assessed these traits using self-reported measures such as McLean Screening Instrument for Borderline Personality Disorder (43) and The Narcissistic Personality Inventory (25).…”
Section: Resultsmentioning
confidence: 99%
“…In keeping with current practices of assessing CEN, we included categorical and dimensional approaches to assessing the symptoms and severity of CEN traits in clinical and general population samples. Examples of dimensional assessment measures include Standardised Assessment of Personality Abbreviated Scale (SAPAS) (24) and Narcissistic Personality Inventory (25).…”
Section: Search Strategymentioning
confidence: 99%
See 2 more Smart Citations